Progressive Muscle Relaxation as a Non-Pharmacological Intervention for Stress, Anxiety, and Quality of Life Among Elderly: A Systematic Review - Setya Rini, Puji (Sahabat Publikasi Kuu, 2026)
Progressive Muscle Relaxation as a Non-Pharmacological Intervention for Stress, Anxiety, and Quality of LifeAmong Elderly: A Systematic Review